Impact of recent heart failure hospitalization on clinical outcomes in patients with severe aortic stenosis undergoing transcatheter aortic valve replacement: an analysis from the PARTNER 2 trial and registries. (22nd May 2020) - Chen, Shmuel; Redfors, Bjorn; Crowley, Aaron; Ben‐Yehuda, Ori; Summers, Matthew; Hahn, Rebecca T.; Jaber, Wael A.; Pibarot, Philippe; Alu, Maria C.; Chau, Katherine H.; Kapadia, Samir; Nazif, Tamim; et al.
Abstract : Aims: Heart failure (HF) hospitalization prior to transcatheter aortic valve replacement (TAVR) is associated with increased post‐procedural mortality. We sought to assess the association between recent (≤6 months) HF hospitalization and long‐term adverse outcomes in patients with symptomatic, severe aortic stenosis, undergoing TAVR in the PARTNER 2 trial and registries. Methods and results: Intermediate to high or even prohibitive risk patients who underwent TAVR in the PARTNER 2 trial and registries were included in the analysis. Clinical outcomes at 30 days and 2 years were compared between patients according to whether they were recently hospitalized for HF, using Kaplan–Meier event rates and study‐stratified multivariable Cox proportional hazards regression models. A sensitivity analysis was conducted using propensity score matching. Of 3988 patients (99.8%) with available information on recent HF hospitalization, 1622 patients (40.7%) were hospitalized for HF symptoms during the 6 months prior to TAVR. After multivariable adjustments, recent HF hospitalization was associated with increased all‐cause mortality at 30 days [adjusted hazard ratio (HR) 1.63, 95% confidence interval (CI) 1.07–2.48, P = 0.02] and 2 years (adjusted HR 1.30, 95% CI 1.13–1.49, P = 0.0003), which was driven by increased cardiovascular mortality. Infective endocarditis rate at 2 years was also higher in patients with recent HF hospitalization (adjusted HR 2.35, 95% CI 1.38–4.01, P = 0.002). These results remained consistent when propensity score matching was used. Conclusion: In a large cohort of patients with severe symptomatic aortic stenosis from the PARTNER 2 trial and registries, all‐cause and cardiovascular mortality as well as infective endocarditis rates at 2 years were higher in patients with recent HF hospitalization.